2017
DOI: 10.3945/cdn.117.000943
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Supplementation Mitigated Food Intake and Growth of Rats Fed a Low-Protein Diet

Abstract: Background: Low protein intake is associated with various negative health outcomes at any life stage. When diets do not contain sufficient protein, phosphorus availability is compromised because proteins are the major sources of phosphorus. However, whether mineral phosphorus supplementation mitigates this problem is unknown, to our knowledge. Objective: Our goal was to determine the impact of dietary phosphorus supplementation on food intake, weight gain, energy efficiency, body composition, blood metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Our results are in line with others, as studies in animals have shown that diets deficient in P are associated with a lower food intake and weight gain (31) . Besides, a comparable rising trend in food intake and EEf was previously demonstrated when P was increased gradually from very low to standard P level of 0.3%, which can be related to the capability of young animals to regulate their food intake in order to support their nutritional requirements for growth and maintenance (30) . However, at higher intakes of P (˃0.3%P), food intake was shown to be inconsistent among different studies.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our results are in line with others, as studies in animals have shown that diets deficient in P are associated with a lower food intake and weight gain (31) . Besides, a comparable rising trend in food intake and EEf was previously demonstrated when P was increased gradually from very low to standard P level of 0.3%, which can be related to the capability of young animals to regulate their food intake in order to support their nutritional requirements for growth and maintenance (30) . However, at higher intakes of P (˃0.3%P), food intake was shown to be inconsistent among different studies.…”
Section: Discussionsupporting
confidence: 68%
“…The Harvard University (USA) software (http://hedwig.mgh.harvard.edu/sample_size/size.html) was used to determine sample size. The sample size for two groups was calculated using input parameters as follows: α error probability of 0•05, power probability of 0•08, 1.5 or 25% difference between the means based on previously determined weight gain data (6.0 ±0.95 g/d) (30) . As a result a total of sample size of 8 rats per group was obtained.…”
Section: Discussionmentioning
confidence: 99%
“… Hammoud et al. (2017) observed that feeding a low-protein diet (10% vs. a control diet at 20%) to rats significantly retarded growth but that these deleterious effects could be largely offset by increasing dietary phosphorus content, both in growth rate and also in body composition.…”
Section: Introductionmentioning
confidence: 98%
“….We have recently found that the addition of phosphorus to a low protein diet (10 % egg white protein) in rats was able to attain a weight gain comparable to that of a normal protein diet (20 %) (3) . Therefore, a study was conducted to investigate whether phosphorus addition can affect growth of rats maintained on incomplete protein diet.…”
mentioning
confidence: 98%
“…For that reason, it should be complemented with a protein source containing the limiting amino acid to match human needs ( 1 ) . Further, wheat is known to contain limited amounts of available phosphorus ( 2 ) .We have recently found that the addition of phosphorus to a low protein diet (10 % egg white protein) in rats was able to attain a weight gain comparable to that of a normal protein diet (20 %) ( 3 ) . Therefore, a study was conducted to investigate whether phosphorus addition can affect growth of rats maintained on incomplete protein diet.…”
mentioning
confidence: 99%